2021
DOI: 10.1002/jib.646
|View full text |Cite
|
Sign up to set email alerts
|

Heat resistance of yeast ascospores and their utilisation for the validation of pasteurisation processes for beers

Abstract: Beers and other low pH beverages are often stabilised by pasteurisation. There is a lack of guidance as to how many pasteurisation units are required for effective treatment of novel products so as to avoid over‐pasteurisation. Yeast are common spoilers of such beverages and some species can produce heat resistant ascospores. As ascospores are more heat tolerant than vegetative cells they are ideal marker organisms for validating the effectiveness of beverage pasteurisation processes. In this study, 63 yeast s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…This suggests that less bitter lagers with low IBU, should be pasteurised with higher PUs than more bitter lagers (medium and high IBU) which can be pasteurised at lower PUs. This was highlighted in our earlier study (6) where an American-style lager (5.6 and 6.9 IBU), which had a significantly lower bitterness than the German lager (25-26 IBU), required higher pasteurisation units. There are no publications investigating the effect of bitterness or hop extracts on the heat resistance of yeast or beer spoilage bacteria and this study is the first report to investigate this topic.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…This suggests that less bitter lagers with low IBU, should be pasteurised with higher PUs than more bitter lagers (medium and high IBU) which can be pasteurised at lower PUs. This was highlighted in our earlier study (6) where an American-style lager (5.6 and 6.9 IBU), which had a significantly lower bitterness than the German lager (25-26 IBU), required higher pasteurisation units. There are no publications investigating the effect of bitterness or hop extracts on the heat resistance of yeast or beer spoilage bacteria and this study is the first report to investigate this topic.…”
Section: Discussionmentioning
confidence: 78%
“…The impact of hop extracts on the behaviour of microorganisms has been explored by many researchers (1)(2)(3)(4)(5) but there is no published data on the impact of hop extracts on the heat resistance of yeast or Lactobacillus. Our earlier work (6) showed that heat resistance of beer spoilage microorganisms was significantly lower in more bitter, German style lagers, and higher in less bitter, American style lagers. Consequently, the calculated pasteurisation units (PU) required for German style (more bitter) were half those for the American style lagers.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Studies on the vulnerability to spoilage of alcohol-free and low alcohol beers have been limited to pasteurisation and the observation that ethanol augments heat in killing microorganisms. Experiments with spoilage yeasts (9,10), yeast spores (9)(10)(11) and bacteria (10,12,13) were shown to be significantly more heat resistant in alcohol-free beer than beers containing alcohol. Consequently, alcohol-free and low alcohol beers in small pack (and large pack) require greater pasteurisation to achieve commercial stability than beers containing alcohol.…”
Section: Introductionmentioning
confidence: 99%